STRATEGI PENGEMBANGAN INDUSTRI BIODIESEL BERBASIS KELAPA DI MALUKU - Sjahrul Bustaman (Badan Penelitian dan Pengembangan Pertanian, 2009)
Strategy of biodiesel development base on coconut in MoluccasBiodiesel is an alternative fuel that can be produced from coconut oil through transesterification process using methanol and sodium hydroxide (NaOH) as catalyst. Nowadays, the development of biodiesel is urgently required to reduce people burden due to the price and the uncertain supply of diesel fuel in small and remote islands. This paper gives the prospect of biodiesel development in Moluccas. The SWOT analysis results in the present study gave strategy for the development of coconut plantations in the Southeast and West of Southeast Moluccas Districts. Other strategy is for the development of biodiesel, that is useful especially for the people who live faraway from Ambon. The utilization of coconut is recommended not only for biodiesel, but also for product diversification. Alternative models/patterns of biodiesel development include a household, a small-micro, a commercial, or a nucleus-plasma pattern. Some steps are required to be carried out by the Government of Moluccas, namely: 1) establish a safe situation in Moluccas as some investors still hesitate to come there, 2) revitalize the existing coconut plantations, 3) establish integrated coconut agribusiness, starting from cultivation aspect, processing, up to marketing in various scales with corporate community orientation, 4) facilitate invest development and strengthening of local institutions, 5) push increase of biodiesel utilization as diesel fuel substitute, and 6) conduct technology transfer, training, and use unemployment people who graduated from the university as partner in business of biodiesel industry.